AGERATUM CONYZOIDES L. (PEMANFAATAN SEBAGAI OBAT DAN BIOAKTIVITASNYA) - Marina Silalahi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2018)
ABSTRACTAgeratum conyzoides or badotan is a wild plants which uses as traditional medicine. This plant has a distinctive aroma similar to